Youth's Intention to Use Mobile Payments Based on TAM Theory - Praswati, Aflit Nuryulia; Saputro, Diky Adi; Sina, Helmia Khalifah; Abbas, Novel Idris (UPN Veteran Yogyakarta, 2023)
Consumer shopping behavior that previously used the brick and mortar method is now shifting to focus on online purchases. Online shopping is made even easier with the mobile payment transaction method. This study aims to explore the behavior of young consumers in using mobile payments when shopping through the view of the Technology Acceptance Model (TAM) theory. Young consumers tend to be curious about new technologies that can make shopping easier for them. This study uses a quantitative method that confirms the relationship between variables that influence the desire of young consumers to use mobile payments. The respondents of this study are young consumers who use mobile payments when shopping. Data collection used questionnaires which were distributed online and analyzed using the PLS SEM method. The results of the study state that the variables service quality, perceived usefulness, perceived ease of use, attitude of use influence behavioral intention to use mobile payments. The characteristics of young consumers have many unique features that will make them even more interesting when further investigated, for example the other side of the ease of use of mobile payments for impulse buying.